Reproductive strategies and group dynamics in the genus Acomys. - Čížková, Barbora (Jihočeská univerzita, 2012)
Reproductive behaviour and aspects of group dynamics in the genus Acomys were studied in the respect to the individuals? physical condition, life history traits and social environment. Three of the presented studies reveal the important effect of social environment on the behaviour of group members to the new-coming male and reproductive behaviour of females (sex ratio of the pups and litter size). The other two studies investigate the costs associated with group living and cooperative breeding in Sinai spiny mice and the factors influencing alloparental behaviour. Results of this Ph.D. thesis reveal several aspects of social and reproductive behaviour of group-living mammals and contribute to the understanding of the formation and maintenance of the societies in general.
Reproductive strategies and group dynamics in the genus Acomys.
Keywords: Spiny mice; reproduction; immigration; litter size; sex ratio; cooperative breeding; sociality